Analisis Pengaruh Perdagangan Internasional Terhadap Pertumbuhan Ekonomi Indonesia - Devina Wistiasari; Febbryan Zhangrinto; Hendro Hendro; Katherine Katherine; Nancy Nancy; Steven Steven (Public Service and Governance Journal, 2023)
International trade greatly affects the economic growth of a country. One indicator of economic growth is the Gross Domestic Product (GDP). This study uses the scientific method approach and hypothesis testing. Types and sources of data used are quantitative data. International Trade has several positive impacts and negative impacts on the Indonesian state. International trade and economic growth are two things that cannot be separated because it is through free markets or international trade that a country's economic growth can increase.